Faktor-Faktor yang Mempengaruhi Stunting di Puskesmas Ngablak di Era Pandemi Covid-19 Tahun 2020 - Sevira, Desan Inti Inka; Priyo, P; Margono, M (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Stunting is a chronic malnutrition condition in which there is a failure to grow in children under five so that the child is too short of the child at his age. Stunting can occur due to exposure to pesticides by farmers that affect thyroid hormone synthesis. Stunting cases in Magelang Regency are most commonly encountered in mountainous areas such as Ngablak Subdistrict, the majority of which work as farmers, in 2020 in Ngablak District which has the highest prevalence of stunting toddlers. The problem faced now is stunting caused by Covid-19, with Large-Scale Social Restrictions (PSBB) impacting on the decline of family finances so that people's purchasing power decreases which results in a crisis of nutrition and child health resulting in an increase in the prevalence of stunting. Aim: To find out the factors that affect stunting in Ngablak Health Center in the era of the Covid-19 pandemic in 2020. Method: The design of the study used cross sectional, with a total sample of 60 stunted toddlers aged 12-36 months. The sampling technique used is purposive sampling. Results: The results of this study showed that the factors that affect the incidence of stunting are maternal education (p =0.012), family economic status (p=0.021), exclusive breast milk history (p=0.006), pregnant woman's nutritional status (p=0.050), frequency of posyandu visits (p=0.002), personal hygiene (p=0.006) and thyroid disorders (p=0.039), while factors that are not related to stunting are the age of pregnant women (p=0.201) and birth distance (p=0.707). Conclusion: Determining factors of stunting events are maternal education, family economic status, exclusive breast milk history, frequency of Integrated Healthcare Center visits, personal hygiene and thyroid disorders. With this research, it is expected that Public health center can make factors related to stunting as a race in order to avoid or prevent the occurrence of stunting in children.